Предмет: Алгебра,
автор: Fransuela
1) 8х2-ху -3у2+(-7х2 + ху -3у2); 2) 8х2-ху -3у2-(-7х2 + ху -3у2); 3) 4х2+2ху +2у2-(8х2 - ху -3у2).
Ответы
Автор ответа:
6
Объяснение:
1) 8х²-ху -3у²–7х² + ху -3у²= х²–6у²
2) 8х²–ху–3у²–(–7х² + ху –3у²)= 8х²–ху–3у²+7х²–ху+3у²= 15х²–2ху
3) 4х²+2ху +2у²–(8х²–ху–3у²)= 4х²+2ху+2у²–8х²+ху+3у²= 5у²–4х²+3ху
Похожие вопросы
Предмет: Русский язык,
автор: kdv1212
Предмет: Английский язык,
автор: anilkakapota
Предмет: Английский язык,
автор: Олечка12345
Предмет: Математика,
автор: МаринеттКатюшка
Предмет: Литература,
автор: вика100408